2011
DOI: 10.1097/prs.0b013e3182174119
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Free Flap Reconstruction for Advanced-Stage Breast Cancer: Is It Safe?

Abstract: Therapeutic, IV.(Figure is included in full-text article.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 46 publications
0
49
0
9
Order By: Relevance
“…Some studies evaluating immediate autologous tissue-based reconstruction before PMRT have reported reasonable rates of complications and satisfactory cosmetic outcomes. 6,29,30,38 However, overall complication rates are often imprecisely defined, as reported overall complications may include complications at both the donor and recipient sites. 39 Even overall complication rates for only the recipient site are not significantly affected by PMRT, especially since radiation therapy is not typically begun until 1 or 2 months after the transfer of the microvascular flap.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies evaluating immediate autologous tissue-based reconstruction before PMRT have reported reasonable rates of complications and satisfactory cosmetic outcomes. 6,29,30,38 However, overall complication rates are often imprecisely defined, as reported overall complications may include complications at both the donor and recipient sites. 39 Even overall complication rates for only the recipient site are not significantly affected by PMRT, especially since radiation therapy is not typically begun until 1 or 2 months after the transfer of the microvascular flap.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, at this point, in patients with advanced stages of breast cancer, immediate breast reconstruction has not been shown to adversely affect local recurrence or overall survival rates. 6,23 Although it has been shown to be oncologically safe to perform immediate breast reconstruction with autologous tissue prior to administration of PMRT, it predisposes patients to the development of a high incidence of fat necrosis, which typically presents as a palpable mass. Any lesion in the breast after breast cancer treatment can be a source of significant anxiety for a breast cancer patient because it may potentially represent a recurrent tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partial necrosis definitions ranged from absolute area, 15,16 proportion of flap lost, 37 to surgical management. [38][39][40] Some articles also described it as any skin loss caused by ischemia.…”
Section: Resultsmentioning
confidence: 99%